1621-P: Lower Osteocalcin Levels Are Associated with Abnormal Adipose Tissue Distribution and Higher Cardiovascular Risk in People with Autoimmune Diabetes - RISI, RENATA; AMENDOLARA, ROCCO; BALENA, ANGELA; MASI, DAVIDE; D'ONOFRIO, LUCA; WATANABE, MIKIKO; GNESSI, LUCIO; MADDALONI, ERNESTO; BUZZETTI, RAFFAELLA (Diabetes (New York, N.Y.), 2024)
Introduction & Objective: Osteocalcin (OCN) plays a role on adipose tissue (AT) and cardiovascular risk (CVR) in subjects with diabetes. Aim: to evaluate the relation between OCN, AT and CVR in autoimmune diabetes (AD). Methods: In this cross-sectional study, body composition was evaluated with DXA-scan in subjects with AD. Adipokines (vaspin, leptin, adiponectin) and OCN were measured. CVR was assessed by the Steno T1 risk engine score (ST1RES). Logistic regression was used to determine predictors of medium/high CVR. Results: Sixty-two patients (median age 49.4 [23-79] years, HbA1c 7.9 [5.7-10.7]%, BMI 25.8[17.2-46.8] Kg/m2) were enrolled. OCN was negatively associated with upper body fat deposition index (UBDFI, p .002 β -.4) and vaspin (p .01, β -.3), positively with adiponectin (p .01 β .3). Patients with lower OCN levels showed higher CVR risk (fig1). A logistic binary regression for including UBFDI, OCN, vaspin, adiponectin as independent variables showed that UBFDI and adiponectin were significant predictors of CVR in AD (R square .356). Conclusion: The association between OCN and adiposity markers suggests its involvement in AT regulation. Nonetheless, patients with lower OCN levels showed higher CVR, suggesting that OCN might be involved in CVR in AD by regulating AT.